Examining the Role Played by Remand Homes Towards Curbing the Rate of Juvenile Delinquency in Kabale Municipality. - Ampurire, Evarine (Kabale University, 2025)
The study examined the role played by remand homes in curbing the rate of juvenile delinquency in Kabale Municipality. The study aimed to establish the causes of juvenile delinquency in Southern Division Kabale Municipality, examining the impact of juvenile behavior in Southern Division Kabale Municipality and establishing the existing strategies used to curb juvenile delinquency in Southern Division Kabale Municipality. The study was conducted in Uganda, and in specifically, southwestern Uganda. Institutionally, looking at Kabale remand home. The centers have long been known for dealing with Child offenders in Uganda and have been responsible for the rehabilitation of Child offenders. This is a new Remand Home, located in southwestern Uganda; within Kabale Municipality. It has a holding capacity of 120 juveniles with 90 males and 30 females. Currently, the facility hosts 36 juveniles 27 being males and 06 females. The study used a descriptive design that is appropriate when collecting information about people’s attitudes, opinions, and habits of a variety of social issues. Qualitative and quantitative research designs were used to collect adequate data. Quantitative data is data presented in the form of descriptive statistics using frequency tables. The study used the Yamane formula (1967) of sample determination to determine the sample size. Self-Administered Questionnaire and interview guide were used as research instruments. The factors or offenses that the inmates committed which led to their incarceration at Kabale remand home and the findings showed as follows; robbery 05%, theft 08%, damage to property were 03%, assault 07%, attempted homicide 05%, and gambling 06%. The causes of juvenile delinquency in Southern Division Kabale Municipality included lack of parental guidance 13%, family breakages 06%, insecurity in families 10%, peer pressure 06%, drug abuse 09%, bad relationship with parents 10%, being orphaned 14%, poverty 12%, social media influence 07% and adolescence phase influence 13%. The study concluded that parents need better understanding in dealing with their children and Teachers, Police and education also play a major role in preventing crimes and there is a need to improve the community and institutions so as to help in curbing the rise of crimes in the society. From the findings, it was concluded that correctional institutions should carefully follow up illegal recreational places that initiate children’s involvement in delinquency and should not only be punitive but also a center for education, training, and rehabilitation this must be seriously taken so as to prevent offenders from being future potential criminals. In addition to this religious institutions and the media should become more flexible to attract the attention of the young generation and teach them how to become law-abiding citizens.